KONSENTRASI LOGAM BERAT PADA MAKROFAUNA BENTIK DI KEPULAUAN KANGEAN, MADURA - Aunurohim Aunurohim; Gilles Radenac; Denis Fichet (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2006)
Study of bioaccumulation of heavy metal at species of macrofauna benthic in Kangean’s archipelago, Madura have been done at February 2004. This study was conducted in the effort data base compiling bioaccumulation of heavy metal, especially in Indonesia. As one of part of “Mussel Watch” program what have been executed by cleft of world angle. Kangean’s archipelago has been selected because its situation was very cloistered and far from modern industrial activity, and also inexistence of data about heavy metal’s accumulation at macrofauna benthic. Sampling has been done in 2 station around island Arjasa (subdivision Arjasa), precisely in Erreng at 6°53’00” S and 115°14’26’’ E and Bilis-Bilis at 6°50’45’’ S and 115°14’54’’ E. Sampling has been conducted by using method of direct collection, and then treated in laboratory to analysis by AAS Spectra AA 250 plus of method flame. Species of Nassarius globosus, Anadara Scapha (big) and Saccostrea cucullata accumulate highest metal of Cu, Cd and Zn (in successively) 192,53 ± 154.65 μg/g dry weight, 13.30 ± 1.55 μg/g dry weight, and 1816.02 ± 367.28 μg/g dry weight.